2016
DOI: 10.1177/0022429416649947
|View full text |Cite
|
Sign up to set email alerts
|

Music Teachers’ Experiences in One-to-One Computing Environments

Abstract: Ubiquitous computing scenarios such as the one-to-one model, in which every student is issued a device that is to be used across all subjects, have increased in popularity and have shown both positive and negative influences on education. Music teachers in schools that adopt one-to-one models may be inadequately equipped to integrate this kind of technology into their classrooms. The purposes of this study were to observe the behaviors and explore the dominant perceptions and concerns of music teachers in scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
(36 reference statements)
0
15
0
1
Order By: Relevance
“…The current status, potential, and challenges of information and communication technologies for music learning are described in the chapter (Bauer, & Mito, 2017). The purpose of the study (Dorfman, 2016) is to study the current ideas and problems of music teachers in schools with one-to-one technology programs. The scientists (Reese, Bicheler & Robinson, 2016) summarized the experience of music teachers using iPad services in their case study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current status, potential, and challenges of information and communication technologies for music learning are described in the chapter (Bauer, & Mito, 2017). The purpose of the study (Dorfman, 2016) is to study the current ideas and problems of music teachers in schools with one-to-one technology programs. The scientists (Reese, Bicheler & Robinson, 2016) summarized the experience of music teachers using iPad services in their case study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Music teachers in schools that adopt one-to-one models may be inadequately equipped to integrate this kind of technology into their classrooms. According to Dorfman’s study (2016), music teachers have expressed their concerns about the adoption of one-to-one technology in their schools and classrooms as they relate to musical goals, extent of integration, and other pedagogical factors. In contrast with teachers, Chen (2015) indicated that the functions clapping and singing score better than the other function feature (stylistic recognition).…”
Section: Introductionmentioning
confidence: 99%
“…A growing trend toward one-to-one technology, defined by classrooms in which each student uses a personal mobile device for individual learning, can be observed in numerous educational fields (Cuban, 2010;Grant, 2011;Dorfman, 2016). Music education research indicates that sustained engagement and the consideration of many different factors (including gender, practice time, and motivation) have the potential to impact the effectiveness of technology in the music classroom (Abramo, 2011;MacIntyre, Potter, & Burns, 2012;Simmons, 2012).…”
Section: Group Piano and Technologymentioning
confidence: 99%
“…The third investigation is an experimental study that was designed to explore the effects of technology tools that represent different possibilities for aural modeling and tempo control on piano achievement during in-class practice sessions. Although one-toone technology implementation has been investigated in the past (Dorfman, 2016;Hahn, in press), little is known about how specific components of technology alter the practice behaviors and performance outcomes of group piano students. Results from a study of current group piano students may encourage piano pedagogues to include technology research and practice in pedagogical and curricular decisions.…”
Section: Research Planmentioning
confidence: 99%
See 1 more Smart Citation